GIS-material for the archaeological project: Stone Age finds within Kulla 1:1 - Local planning - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
The Swedish National Heritage Board's contract archaeology division, UV Öst, has performed several stage 2 surveys and a preliminary investigation within Kulla 1:1, Krokek parish, Norrköping municipality in May and June 2005. The municipality is working on a local plan for the area on which previous surveys have discovered a Stone Age settlement and a medieval village site (UV2). UV Öst surveyed three areas (Object 1-3) and performed a preliminary investigation of UV 2. Except for several stray finds of Stone Age character within Object 1, no prehistoric or historical features were found. The location of Object 2 turned out to already be developed, and UV 2 was, after removal of the top soil, interpreted as having been destroyed in modern times. UV Öst thus suggests no further archaeological measures within these areas.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the surveys was to determine whether the survey areas contained any archaeological remains. The purpose of the preliminary investigation was to establish the character, dating and extent of the archaeological remains. The results of the surveys and the investigation are to form a basis for future decisions by the County Administrative Board concerning the matter.

The ZIP file consist of Shapefiles and an Access database with information about trenches, features, finds and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har under maj och juni 2005 genomfört arkeologiska utredningar, etapp 2, samt en arkeologisk förundersökning inom Kulla 1:1, Krokeks socken, Norrköpings kommun. Kommunen arbetar med detaljplan i området som vid en tidigare utredning visat sig inrymma en stenåldersboplats samt platsen för en medeltida bytomt (UV 2). UV Öst genomförde utredning inom tre områden (Objekt 1-3) samt förundersökning inom UV 2. Utöver ett flertal spridda lösfynd av stenålderskaraktär i åkerjord inom Objekt 1, påträffades inga förhistoriska eller kulturhistoriskt intressanta anläggningar. Platsen vid Objekt 2 visade sig redan vara bebyggd och UV 2 bedömdes efter avbaning vara förstörd i modern tid. UV Öst föreslår därför inga ytterligare antikvariska åtgärder inom de aktuella områdena.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med de arkeologiska utredningarna var att fastställa om fornlämningar var belägna inom utredningsområdena. Syftet med den arkeologiska förundersökningen var att fastställa fornlämningens art/karaktär, ålder och utbredning. Resultaten från utredning och förundersökning skulle syfta till att utgöra underlag för Länsstyrelsens vidare bedömningar i ärendet.

ZIP-filen innehåller shapefiler samt en Access-databas vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Stenåldersfynd inom Kulla 1:1 - Detaljplansarbete
Keywords: stone age; stenålder; finds; fynd; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive